Les accidents de circulation dans la ville de Kisangani et l’état des lieux de leur indemnisation : Etude menée dans les communes de Kabondo et Makiso de 2013 à 2015 - kaputula ninga, stephane (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Town of Kisangani recorded a lot accident of accidents of circulation during the period understood between 2013 and 2015. This tragedy undermined many citizens of the city wo knew serious injuries and important material damages or even of the losses in human lives.It is of principle that the Congolese state through its specialized services is supposed to help victims of these accidents in order to repair the damages that they underwent.It is this article interrogates the reasons to the basis to the circulation accidents in the city of Kisangani He/it temps to value the level of repair of these damages otherwise and propose some tracks in order to improve the level of indemnification of the damages undergone in case of circulation accident.